Peranan Orangtua dalam Memberikan Pengawasan terhadap Penggunaan Media Elektronik bagi Anak di Desa Cabbeng, Kec. Dua Boccoe, Kab. Bone - Anwar, Hasni B (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This paper examines the Role of Parents in providing Oversight of the use of electronic Media for children in the village of Cabbeng, Kec. Two Boccoe, Kab. Bone. The results showed that these forms of supervision of parents against the use of electronic media namely a) the giving of advice and guidance with the intent as a form of accountability for parents against children and children can receive guidance and advice because the decision agreed upon together. The elderly easy to control his son and the son himself receptive to strikes from parents. b) limitation on the use of electronic media namely control or supervise all activities or activities undertaken by children either directly or indirectly. Parental controls against his son is usually preferred in excessive problems in using electronic media. and c) fulfillment of the needs of the child that is the fulfillment of the needs of the child, with all the excessive desires makes the children not to be held responsible and confident. Parents tend to give a lot of freedom on his children by accepting and know all the behaviors, actions and guiding children, but less demanding attitude of responsibility and regularity of child behavior.